Iconicity in Language An Encyclopaedic Dictionary. - Moreno Cabrera, Juan Carlos (Cambridge Scholars Publisher, 2020)
In linguistics, as in semiotics, iconicity is the conceived similarity between the form of a linguistic sign and its meaning. This book covers all aspects of linguistic iconicity in both spoken and signed languages, including definitions of all the relevant concepts and explanations of significant iconic words and expressions, and brief summaries of the contents and main proposals of 30 significant works in the history of iconicity research. It also provides definitions and exemplifications of the principles governing linguistic iconicity and brief overviews of iconic words and expressions in.